2022
DOI: 10.1590/1806-9479.2021.250643
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of El Niño southern oscillation on hedge strategies for Brazilian corn and soybean futures contracts

Abstract: Climate influences the variations in soybean and corn prices; thus, we assessed the relationship between the El Niño Southern Oscillation (ENSO) with soybean-to-corn price ratio to determine potential impacts on price risk management. The commercial areas of Passo Fundo (RS), Cascavel (PR), Maringá (PR), Uberlândia (Triângulo Mineiro), and Sorriso (MT) covered in the study were chosen according to the MAPA edaphoclimatic classification. To estimate the effectiveness and optimal hedge ratio, the static and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(47 reference statements)
0
0
0
Order By: Relevance
“…By incorporating the ENSO climate component into the optimal hedging ratio model, the impact of climate on hedging and cross-hedging strategies can be verified. Through this analysis, it was found that the adoption of appropriate hedging strategies can mitigate the price risk of the corn spot market [5]. This is supported by the practices of several companies, including Bunge, in the United States.…”
Section: Hedging Strategies In the Food Marketmentioning
confidence: 82%
See 1 more Smart Citation
“…By incorporating the ENSO climate component into the optimal hedging ratio model, the impact of climate on hedging and cross-hedging strategies can be verified. Through this analysis, it was found that the adoption of appropriate hedging strategies can mitigate the price risk of the corn spot market [5]. This is supported by the practices of several companies, including Bunge, in the United States.…”
Section: Hedging Strategies In the Food Marketmentioning
confidence: 82%
“…The corporation's strategy to mitigate interest rate risk is to secure upcoming rates by choosing suitable interest rate swaps or option contracts based on its fixed-rate and floating-rate debt profile. This approach minimizes interest expense and debt valuation sensitivity to fluctuations in interest rates [6].…”
Section: Hedging Strategies In the Food Marketmentioning
confidence: 99%